The Effect of Bariatric Surgeries on Nonalcoholic Fatty Liver Disease - Hassanian, Mazen (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: A review of published data addressing hepatic histopathological, metabolical, and functional changes following gastric banding, sleeve gastrectomy, gastric bypass surgery, and biliopancreatic with duodenal switch surgeries on nonalcoholic fatty liver disease (NAFLD). NAFLD is currently the most common chronic liver disease. Owing to the strong relationship between obesity and NAFLD, the idea of weight reduction as a method to treat NAFLD has rapidly emerged. Bariatric surgery has proved to be the most efficient method for weight reduction; hence, their beneficial effects on NAFLD have been evaluated by several studies. A literature review of published data was performed during the years 2012-2014 using PubMed with the following key words: Bariatric, NAFLD, steatosis, sleeve gastrectomy, gastric bypass, gastric banding, biliopancreatic diversion with duodenal switch, obesity, and insulin resistance (IR). Exclusion criteria were non-English articles and inherited NAFLD, pregnancy-induced NAFLD, and children. The majority of published data are in favor of indicating that bariatric surgeries improve the histologic and metabolic changes associated with NAFLD. The suggested mechanisms are: The reversal of IR, reduction of inflammatory markers, and improved histological features of NAFLD. Accordingly, bariatric surgeries are potentially one of the future methods in treating patients with morbid obesity and NAFLD. However, some questions remain unanswered, such as whether timing of surgery, type of surgery most effective, and whether bariatric surgeries are capable of curing the disease. Long-term and well-designed prospective studies are needed to address these issues.